Donors assessment methods and the institutional capacity of grassroots organizations in Egypt. - Henein, Angie Atef Sideek (AUC Knowledge Fountain, 2016)
Donors are increasingly addressing the institutional capacity of partner grassroots organizations using various tools and methods. This study aims to analyze donors’ assessment methods and tools and the capacity building efforts of four key donors in Egypt. Using qualitative research, the study looks at donors’ assessment tools and methods before, during, and after the cooperation along with efforts in building the institutional capacities. The study finds that the project size is key to the level of donor engagement in the capacity building of grassroots organizations. Donors efforts primarily focus on managerial and technical capacities along with skills of proposal writing and financial management. These assessment and capacity building efforts stop at the institutional capacity level and do not take a holistic approach by looking at issues of internal governance and policies. There is also a clear absence of systems assessing the impact of such capacity building efforts by donors